KHAZANAH KITAB KUNING: MEMBANGUN SEBUAH APRESIASI KRITIS - Zaini Dahlan (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
This article aims to uncover the treasures of the yellow book in a historical perspective. The methodology used in this article is the research methodology putaka or libraryresearch.The authors conclude that there are at least three characters in the writer of the 20th century who wrote the Yellow Book. Firstly, namely Ahmad Khatib (d. 1915) Minangkabau Indonesia- -bapak Islamic reformers who also was a disciple of Sheikh Bantani Nawawi (d. 1896). Second, Kyai Mahfouz Termas (d. 1919-20). The third was Muhammad Hasyim Asy'ari (1287-1366 / 1870-1947). There are two important points to explain the position and significance of the Yellow Book in schools. The first point, the authenticity of the Yellow Book for pesantren is a reference to abortion has been unquestionable. The fact that the Yellow Book was written long ago and continues to be used from time to time indicate that the book has been verified in history. The second point, Yellow Book is very important for schools to facilitate the process of deep religious understanding so as to formulate a fresh explanation but not ahistorical about the teachings of Islam, the Qur'an and Hadith. A brief description of the tradition over the Yellow Book shows how schools as an institution needs to work hard to maintain his identity while continuing to hold the development of tradition and orientation.